ANALISIS DAN PERENCANAAN PENERAPAN ENTERPRISE RESOURCE PLANNING (ERP) PADA YAYASAN PENDIDIKAN PRABUMULIH - Ahmat Josi (Jurnal Informatika, 2016)
Increasingly fierce competition between universities in Indonesia provide university to give the best service to student and stakeholder, with increasing competition make university apply many new technologies like ERP. ERP is one of them system that can integrating exiting systems in university, with ERP academic service which exists in university will more maximum and easy to be controlled, with ERP Prabumulih Education Foundation will have value added in promotion, so it can improve interest prospective student.  Keywords— Perguruan Tinggi, ERP, Yayasan Pendidikan Prabumulih